O2-S1.06 Community responses to an HIV epidemic in South India: knowledge, moral panic and cultural inertia. (10th July 2011) - Bradley, J; Rajaram, S; Ramesh, BM; Bhattacharjee, P; Isac, S; Lobo, A; Moses, S; Blanchard, J; Washington, R; Alary, M
Abstract : Background: Studies have shown that as communities face serious threats to traditional values, such as that posed by HIV, cultural inertia may result, whereby existing trends towards more liberalised views of sexuality are stalled, particularly among the educated and youth. We examined changes in attitudes around HIV in Bagalkot district, south India, between 2003 and 2009. Methods: General population surveys were conducted in 2003 and 2009, among approximately 6600 randomly sampled men and women in 10 villages and 20 urban blocks. Questions about HIV knowledge, sexuality, gender and condoms were included. Results: Knowledge of HIV increased from 77% in 2003 to 88% in 2009, and condom awareness increased significantly (37.4%–65.4%). However, in 2009, only 23% of people mentioned condoms spontaneously as a means of preventing transmission (an increase from 8% in 2003). There was an increase in those who thought sex workers should be compulsorily tested for HIV (63.0% vs 73.5%, p=0.01). An increasing number of people agreed that it is wrong to talk about sex" (24.2% vs 29.2%, p=0.05), especially women (21.9% vs 32.4%, p<0.01). There was an increase in those who thought it "wrong to talk about AIDS in a respectable family" (16.4% vs 0.22.1%, p=0.01), largely among urban women, youth and the more educated, and more in 2009 thought it improper for respectable people to discuss condoms (5.5% vs 17.9%, p<0.01). In 2003, 11.8% agreed that "access to condoms promotes promiscuity", increasing to 29.5% in 2009 (p<0.01). Men, educated people, urbanites and young people under 25 were the most likely to believe this. Sex education was thought to be equally damaging, especially among women and young people, with more agreeing that it promotes sexual activity and promiscuity in 2009 than in 2003 (19.3% vs 30.2%, p<0.01). Conclusions: Although scapegoats (in the form of sex workers) were increasingly identified by the community, stigma towards those with HIV appeared to have reduced significantly. Despite increased knowledge and positive changes around stigma, fear of change to cultural mores was apparent, with unwillingness to embrace openness and discuss sexuality. Young and educated respondents appeared to be the most regressive thinkers, reflecting a cultural inertia that mirrors studies of other threats to traditional societal values. More effort is required to educate young people about healthy sexuality, openness and safe sex.